北極域における雲と赤外放射量の特徴 - 竹岡, 遼; 西中, 規実子; 井上, 梓; 久慈, 誠; 矢吹, 正教; 塩原, 匡貴; Takeoka, Haruka; Nishinaka, Kimiko; Inoue, Azusa; Kuji, Makoto; Yabuki, Masanori; Shiobara, Masataka (2013)
We investigated characteristics of cloud and long-wave downward radiation during the year 2008 at Ny-Ålesund using Micro Pulse LIDAR (MPL) and the pyrgeometer in Baseline Surface Radiation Network (BSRN). We found that long-wave downward radiation was lower as cloud base height was higher on January 1, when mean cloud amount was 10. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object